2016
DOI: 10.1111/petr.12692
|View full text |Cite
|
Sign up to set email alerts
|

Combined plerixafor and granulocyte colony‐stimulating factor for harvesting high‐dose hematopoietic stem cells: Possible niche for plerixafor use in pediatric patients

Abstract: PB is a source of HSC, especially for autologous HCT in solid tumors. However, there is a risk of failing to achieve the target number of SC after mobilization with growth factors alone in patients who were heavily pretreated with chemotherapy or those in need for tandem transplants. SC were harvested from seven pediatric patients with solid tumors who were in need of autologous HCT following combination GCSF and plerixafor. Six of them received plerixafor after failing to achieve enough SC with GCSF only, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(54 reference statements)
3
9
0
Order By: Relevance
“…As in other pediatric studies that have shown the utility of plerixafor to facilitate PBSC mobilization with success rates ranging from 57%‐100%, 2,3,5–7,15–20,23–27 we observed adequate CD34+ yield in 87.2% of recipients, with no difference between Group A or B patients (84.2% vs 89.2%) groups. In the phase I part of their study (n = 27), Morland et al determined the dose of plerixafor in children to be 240 μg/kg which was the dose received by majority of patients in our cohort.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As in other pediatric studies that have shown the utility of plerixafor to facilitate PBSC mobilization with success rates ranging from 57%‐100%, 2,3,5–7,15–20,23–27 we observed adequate CD34+ yield in 87.2% of recipients, with no difference between Group A or B patients (84.2% vs 89.2%) groups. In the phase I part of their study (n = 27), Morland et al determined the dose of plerixafor in children to be 240 μg/kg which was the dose received by majority of patients in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…4 Risk factors for poor mobilization include multiple prior chemotherapy cycles, exposure to platinum or alkylating agents, and prior radiation therapy or a primary diagnosis of neuroblastoma, medulloblastoma or relapsed/refractory Hodgkin lymphoma (HL). [4][5][6] Plerixafor, a bicyclam derivative and a reversible CXCR4 receptor antagonist, disrupts the interaction of SDF-1 with its receptor CXCR4 on the surface of stem cells, causing release of stem cells from the marrow. 1 Plerixafor along with GCSF has been successfully used in adults either after failure of chemotherapy and cytokinebased mobilization, or as a preemptive agent if peripheral blood (PB) CD34+ cell counts are inadequate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in patients responding poorly to G-CSF (< 20 × 10 6 /L CD34+ cells in PB), pre-emptive plerixafor treatment led to a final yield equivalent to a rescue strategy administered to patients with insufficient leukapheresis [50]. Several additional studies have endorsed the use of plerixafor in autologous transplantation for diabetic patients [51] and pediatric patients [52,53,54], whereas other articles have supported its use in elderly patients and those with renal insufficiency [55,56]#.…”
Section: Resultsmentioning
confidence: 99%